Human Dendritic Cells: Their Heterogeneity and Clinical Application Potential in Cancer Immunotherapy - Patente, Thiago A.; Pinho, Mariana P.; Oliveira, Aline A.; Evangelista, Gabriela C. M.; Bergami-Santos, Patrícia C.; Barbuto, José A. M. (Frontiers in Immunology, 2019)
Dendritic cells (DC) are professional antigen presenting cells, uniquely able to induce naïve T cell activation and effector differentiation. They are, likewise, involved in the induction and maintenance of immune tolerance in homeostatic conditions. Their phenotypic and functional heterogeneity points to their great plasticity and ability to modulate, according to their microenvironment, the acquired immune response and, at the same time, makes their precise classification complex and frequently subject to reviews and improvement. This review will present general aspects of the DC physiology and classification and will address their potential and actual uses in the management of human disease, more specifically cancer, as therapeutic and monitoring tools. New combination treatments with the participation of DC will be also discussed.